2014
DOI: 10.1007/s10995-014-1638-1
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence, Marital Control, and Family Planning, Maternal, and Birth Outcomes in Timor-Leste

Abstract: Patriarchal traditions and a history of armed conflict in Timor-Leste provide a context that facilitates violence against women. More than a third of ever-married Timorese women report physical and/or sexual domestic violence (DV) perpetrated by their most recent partner. DV violates women's rights and may threaten their reproductive health. Marital control may also limit women's reproductive control and healthcare access. Our study investigated relationships between DV and marital control and subsequent famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 16 publications
4
27
1
Order By: Relevance
“…; Meiksin et al. ). The significant association between men's educational attainment and greater odds of reporting of total unmet need, unmet need for spacing, and unmet need for limiting are consistent with the findings of Elfstrom and Stephenson (), who suggest that increased educational attainment for men does not necessarily result in greater autonomy for women and “may even result in greater gender inequalities” (p. e40670).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Meiksin et al. ). The significant association between men's educational attainment and greater odds of reporting of total unmet need, unmet need for spacing, and unmet need for limiting are consistent with the findings of Elfstrom and Stephenson (), who suggest that increased educational attainment for men does not necessarily result in greater autonomy for women and “may even result in greater gender inequalities” (p. e40670).…”
Section: Discussionmentioning
confidence: 97%
“…In the domain of gender norms and inequalities, increased justification of violence may negatively affect a woman's autonomy and decrease her ability to obtain desired contraception (Diop-Sidibe, Campbell, and Becker 2006;Elfstrom and Stephenson 2012;Haque et al 2012;Meiksin et al 2015). The significant association between men's educational attainment and greater odds of reporting of total unmet need, unmet need for spacing, and unmet need for limiting are consistent with the findings of Elfstrom and Stephenson (2012), who suggest that increased educational attainment for men does not necessarily result in greater autonomy for women and "may even result in greater gender inequalities" (p. e40670).…”
Section: Discussionmentioning
confidence: 99%
“…11 Meiksin R et al reported that overall women who experienced domestic violence were more likely than other rural women to have an unplanned pregnancy, fewer than four antenatal visits or a baby born smaller than average. 13 On the other hand Alio AP et al reported that women who had experienced domestic violence were significantly more likely to report that they had used contraception compared to women who hadn't experienced domestic violence. 14 Among the women's empowerment indicators decision on her own health and decision to visit friends/relatives was associated with current usage of modern contraceptive methods.…”
Section: Discussionmentioning
confidence: 99%
“…Newborns of victims of violence were more likely to have low birth weight (Bailey, 2010;Meiksin et al, 2015;Pavey et al, 2014;Shah & Shah, 2010), preterm birth (Bailey, 2010;Pavey et al, 2014;Shah & Shah, 2010), respiratory problems, and neonatal hospitalization (Pavey et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%